Development of HOTS-Based Final Semester Assessment Questions in the Al-‘Ashri Arabic Textbook for 10th-grade Students of Islamic Senior High School - Masrifah, Khusnul; Ahsanuddin, Mohammad (Arabiyatuna: Jurnal Bahasa Arab, 2025)
This study aimed to develop and validate a Higher-Order Thinking Skills (HOTS)–based assessment instrument for Arabic language learning using the Al-‘Ashri textbook for 10th-grade students at an Islamic Senior High School. The research employed a Research and Development (R&D) design following the 4D model: Define, Design, Develop, and Disseminate. Several research instruments were utilized, including: (1) a needs analysis questionnaire and interview guidelines to identify issues in existing Arabic learning assessments; (2) validation sheets for material experts and linguists to evaluate content, construct, and language validity; (3) a HOTS-based test instrument consisting of 36 multiple-choice and 4 essay questions developed according to Bloom’s revised taxonomy (C4–C6); and (4) data analysis tools to measure validity, reliability, item difficulty, and discrimination indices processed using SPSS. Each instrument served a distinct purpose: the questionnaire and interviews gathered empirical data on field needs, the validation sheets assessed the feasibility and accuracy of content and language, and the HOTS-based test was empirically tested on 34 students to examine its psychometric properties. The material validation achieved a score of 94% and the language validation 84%, both categorized as “highly feasible.” Empirical testing showed that all items were valid (r-value > r-table = 0.338), with a reliability coefficient of r = 0.88 (high), item difficulty indices ranging from 0.15–0.85 (moderate), and discrimination indices indicating 38.89% good and 61.11% moderate items. These findings confirmed that the developed HOTS-based assessment instrument was valid, reliable, and effective for evaluating higher-order thinking skills in Arabic language learning at the senior high school level.